Single-dose versus multi-dose vaccine vials for immunization programmes in developing countries - Drain Paul K.; Nelson Carib M.; Lloyd John S. (The World Health Organization, 2003)
Excessive vaccine wastage and safety concerns have prompted the international health community to develop and supply vaccines in formats other than the standard multi-dose vial. This article presents a programmatic and economic comparison of the major differences between the multi-dose vials and single-dose formats used for immunization services in developing countries. Multi-dose vials, in general, sell at a lower per-dose price and occupy less cold-chain capacity than single-dose formats. However, higher wastage rates may offset these benefits, especially for more expensive vaccines. Singledose formats offer several important programmatic benefits, such as increased vaccination opportunities and improved vaccine safety. One single-dose format, the prefilled auto-disable (AD) device, provides additional injection safety and convenience features because it physically combines the vaccine and AD syringe. Selecting the appropriate vaccine presentation will depend on many factors. However, multi-dose vials are likely to be most appropriate for cheaper vaccines and in settings where cold-chain storage capacity is restricted. Single-dose formats will be most appropriate for more expensive vaccines and where there are problems with unsafe injection practices. Prefilled AD injection devices will be particularly useful in expanding outreach services while eliminating the possibility of needle reuse.